2006
DOI: 10.1111/j.1540-8175.2006.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Study of Cardiac Morphological and Functional Changes before and after Parturition in Pregnancy‐Induced Hypertension

Abstract: Purpose: To investigate the cardiac morphological and functional changes by echocardiography, before and after parturition in patients with pregnancy-induced hypertension (PIH). Methods: The parameters related to cardiac morphology and left ventricular diastolic and systolic functions were compared before and after parturition in 32 patients with PIH and 24 normal pregnant (NP) women. Results: Compared with NP women, the PIH patients had greater diameters of left atrium and left ventricle in end-diastole (LAd:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…33,35,38,40,41,45,50 Hypertrophy in preeclampsia tends to be of the concentric type 50 and has been shown in preterm 33,40,46 and term preeclampsia. 41,45,46,55 In 1 study, concentric LV remodeling was demonstrated at 20 to 23 weeks of gestation in 33% of women who subsequently developed preeclampsia. 27 In women who progressed to preeclampsia from GH, 27% had abnormal LV structure and function at the time of echocardiography.…”
Section: Cardiac Structure and Remodelingmentioning
confidence: 99%
See 4 more Smart Citations
“…33,35,38,40,41,45,50 Hypertrophy in preeclampsia tends to be of the concentric type 50 and has been shown in preterm 33,40,46 and term preeclampsia. 41,45,46,55 In 1 study, concentric LV remodeling was demonstrated at 20 to 23 weeks of gestation in 33% of women who subsequently developed preeclampsia. 27 In women who progressed to preeclampsia from GH, 27% had abnormal LV structure and function at the time of echocardiography.…”
Section: Cardiac Structure and Remodelingmentioning
confidence: 99%
“…3,17,58,60,61 A greater reduction in E/A has been shown in GH than in pregnancy unaffected by hypertension. 24,35,47,48,55 Diastolic function is also impaired in preeclampsia, 40,46,53 where the usual reduction in E/A is exaggerated.…”
Section: Diastolic Functionmentioning
confidence: 99%
See 3 more Smart Citations